2022
DOI: 10.1371/journal.pone.0273345
|View full text |Cite
|
Sign up to set email alerts
|

Depression and associated factors among older adults in Bahir Dar city administration, Northwest Ethiopia, 2020: Cross-sectional study

Abstract: Background Depression is the most common psychiatric condition among older adults, and it goes unnoticed by individuals themselves and is under-diagnosed by clinicians due to the misconception that these are normal parts of aging. However, the problem is not properly addressed in Ethiopia. This study aimed to determine the prevalence and associated factors of depression among the older adults in Bahir Dar city. Methods A community-based cross-sectional survey was conducted among 423 older adults in Bahir Dar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 44 publications
0
11
1
1
Order By: Relevance
“…On the other hand, our results are greater than those of studies done in the United States of America, 22% [ 27 ], China 22.4% [ 28 ], Netherlands 30.9% [ 29 ] and Canada 37% [ 12 ]. This discrepancy could be due to the difference in socioeconomic status and the living standard of the study participants in which low socioeconomic status is 1.5 times the high risk of developing depression as compared to high socioeconomic status [ 1 ].…”
Section: Discussioncontrasting
confidence: 93%
“…On the other hand, our results are greater than those of studies done in the United States of America, 22% [ 27 ], China 22.4% [ 28 ], Netherlands 30.9% [ 29 ] and Canada 37% [ 12 ]. This discrepancy could be due to the difference in socioeconomic status and the living standard of the study participants in which low socioeconomic status is 1.5 times the high risk of developing depression as compared to high socioeconomic status [ 1 ].…”
Section: Discussioncontrasting
confidence: 93%
“…Since depression is a common disease in the elderly, the factors that increase depression are exceptionally diverse. Previous studies have shown that depression in the elderly is closely related to depression, including gender, age, education level, chronic disease, social support, health promotion behavior, leisure life satisfaction, and medical expenses 12 , 13 . Concerning elderly depression in Ethiopia, one of the low-income countries, two out of five elderly people suffer from depression.…”
Section: Introductionmentioning
confidence: 99%
“…This trend is projected to continue, with predictions suggesting that by 2050, there will be around 340 million elderly individuals in India [ 2 ]. This increase in the elderly population presents several challenges, including increased demand for healthcare services, elevated risk of chronic diseases, and decreased workforce participation [ 3 , 4 ]. It also underscores the need for policies and interventions aimed at improving the well-being and quality of life of the elderly population in India [ 5 ].…”
Section: Introductionmentioning
confidence: 99%